Antimicrobial action of chromatin extracellular traps released by neutrophils of rainbow trout, Oncorhynchus mykiss (Walbaum, 1792) - Van, Andre P; Bron, James E; Desbois, Andrew P (Fish & Shellfish Immunology, 2023)
First paragraph: Chromatin extracellular traps (ETs) are released in vitro by certain fish polymorphonuclear leucocytes (PMNs), including neutrophils, in response to various chemical and biological stimuli such as bacterial cells and components like flagellin and lipopolysaccharide [[1], [2], [3], [4]]. For mammals in particular, ETs have been shown to exert antimicrobial properties and function as part of the innate response [5,6]. However, there are few studies on the antimicrobial actions of ETs released by fish, with these properties reported for ETs in immune cell suspensions prepared from common carp (Cyprinus carpio) [7], turbot (Scophthalmus maximus) [8,9] and tongue sole (Cynoglossus semilaevis) [1]. In contrast, some studies failed to provide evidence for antibacterial activities, including those examining tongue sole ETs against Edwardsiella tarda [1] and Atlantic salmon (Salmo salar) ETs against Aeromonas salmonicida [4], indicating complexity in the interactions between bacteria and the actions of the ETs. This present study investigated whether ETs released by neutrophils of rainbow trout (Oncorhynchus mykiss) exert antibacterial activity against the important finfish pathogen, Vibrio anguillarum.